PENERAPAN SISTEM IRIGASI SPRINKLE PADA KEGIATAN BUDIDAYA BAWANG MERAH (Allium Cepa.L) STUDI KASUS DI KECAMATAN REJOSO, KABUPATEN NGANJUK - Fibriani, Suwinda; Krismiratsih , Fitri; R, Ika Puspitasari D (Fruitset Sains : Jurnal Pertanian Agroteknologi, 2025)
Rejoso Rejoso sub-district in Nganjuk district is known as a high-productivity shallot center. One of the important factors affecting crop yields is the irrigation system used. The increasing scarcity of water resources due to climate change and growing intersectoral demand has made irrigation a strategic issue in the national agricultural sector. This study aims to compare the effectiveness of conventional irrigation systems with sprinkle irrigation in shallot (Allium cepa L.) cultivation. The method used was a one-factor Completely Randomized Design (CRD) with five treatments, namely with a water volume of P1 = Manual watering, P2 = 75%, P3 = 100%, P4 = 150%, P5 = 200% of optimal needs. Parameters observed included plant height, number of leaves per clump, and tuber wet weight. Results showed that treatment P5 (200%) of water requirement and conventional watering gave the best growth and production results. The sprinkle irrigation system proved to be more efficient in water use, provided even water distribution, and reduced labor requirements. Thus, sprinkle irrigation can be an appropriate technology solution to support shallot cultivation as well as efficient and sustainable water management.